2015
DOI: 10.1080/07315724.2014.966396
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Android and Gynoid Body Adiposity via a Three-dimensional Stereovision Body Imaging System and Dual-Energy X-ray Absorptiometry

Abstract: Objective Current methods for measuring regional body fat are expensive and inconvenient compared to the relative cost-effectiveness and ease-of-use of a stereovision body imaging (SBI) system. The primary goal of this research is to develop prediction models for android and gynoid fat by body measurements assessed via SBI and dual-energy x-ray absorptiometry (DXA). Subsequently, mathematical equations for prediction of total and regional (trunk, leg) body adiposity were established via parameters measured by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 33 publications
2
27
0
Order By: Relevance
“…Body composition models from 3D features calibrated using DXA data validated well, similar to those reported by Lee et al , 7,18 especially in light of the different body composition measurement methods used (DXA calibration data and BIA validation data in our study and DXA and MRI data in Lee’s studies). In particular, our whole-body fat mass prediction model showed strong fit to the calibration data (R 2 = 0.95), matching the equivalent Lee model (R 2 = 0.95).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Body composition models from 3D features calibrated using DXA data validated well, similar to those reported by Lee et al , 7,18 especially in light of the different body composition measurement methods used (DXA calibration data and BIA validation data in our study and DXA and MRI data in Lee’s studies). In particular, our whole-body fat mass prediction model showed strong fit to the calibration data (R 2 = 0.95), matching the equivalent Lee model (R 2 = 0.95).…”
Section: Discussionsupporting
confidence: 88%
“…In particular, our whole-body fat mass prediction model showed strong fit to the calibration data (R 2 = 0.95), matching the equivalent Lee model (R 2 = 0.95). 7 Our visceral fat prediction model showed moderately strong association (R 2 = 0.75), similar to Lee (R 2 = 0.72). 13 …”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Lee et al [34] reported that inclusion of the 3D-determined waist-to-hip ratio significantly improved multiple regression equations to predict MRI-estimated visceral AT but neither total abdominal AT nor subcutaneous AT. They also used 3D imaging to assess fat patterning of adults [35]. Compared to the usual demographic information (e.g., gender, age, and ethnicity) and standard anthropometric measurements (e.g., weight, height, and waist circumference), the inclusion of 3D body image data (e.g., regional volumes, circumferences and sagittal thicknesses) improved the precision, relative to DXA, to 2 kg and 0.2% for android and 3.2 kg and 0.4% for gynoid AT mass and % fat, respectively.…”
Section: Discussionmentioning
confidence: 99%